Association between mitral regurgitation and clinical outcome after endovascular thrombectomy in stroke patients. (2nd July 2020) - Aoki, Junya; Suzuki, Kentaro; Kanamaru, Takuya; Katano, Takehiro; Sakamoto, Yuki; Kutsuna, Akihito; Suda, Satoshi; Nishiyama, Yasuhiro; Kimura, Kazumi
ABSTRACT: Objective: Some hyperacute stroke patients have unfavorable outcomes after endovascular thrombectomy (EVT) despite successful recanalization. We hypothesized that a cardiac parameter, moderate-to-severe mitral regurgitation (MR), might decrease the rate of favorable clinical outcome after EVT in patients with atrial fibrillation (AF). Method: From our prospective EVT registry, AF patients who underwent transthoracic echocardiography (TTE) were retrospectively analyzed. Based on the presence of moderate-to-severe MR, patients were assigned to either significant MR or nonsignificant MR group. The severity of MR was determined by the ratio of the color Doppler jet area to the left atrial area in mid-systole. Moderate-to-severe MR was estimated to be at a ratio of >20%. Favorable outcome was defined as having a modified Rankin Scale score of 0–1 at 3 months. Result: 127 patients with AF who underwent TTE were included in the study. TTE results found that 25 (20%) patients had significant MR. Patients with significant MR were older (p = 0.051) and had enlarged left (p = 0.015) and right (p = 0.002) atria. Tricuspid and aortic regurgitation (p = 0.007 and 0.043, respectively) were more severe in significant MR group. At 3 months, favorable outcomes were 11% in the significant MR group and 26% in the non-significant MR group (p = 0.031). Multivariate regression analysis reported that moderate-to-severe MR was a negative predictor of favorable outcome (odds ratio = 0.14; 95% confidence interval = 0.02, 0.84; p = 0.031). Conclusions: Significant MR might prevent the clinical recovery of AF patients.